Abcc6 Null Mice—a Model for Mineralization Disorder PXE Shows Vertebral Osteopenia Without Enhanced Intervertebral Disc Calcification With Aging - Boneski, Paige K.; Madhu, Vedavathi; Tomlinson, Ryan E.; Shapiro, Irving M.; van de Wetering, Koen; Risbud, Makarand V. (Frontiers in Cell and Developmental Biology, 2022)
Chronic low back pain is a highly prevalent health condition intricately linked to intervertebral disc degeneration. One of the prominent features of disc degeneration that is commonly observed with aging is dystrophic calcification. ATP-binding cassette sub-family C member 6 (ABCC6), a presumed ATP efflux transporter, is a key regulator of systemic levels of the mineralization inhibitor pyrophosphate (PPi). Mutations in ABCC6 result in pseudoxanthoma elasticum (PXE), a progressive human metabolic disorder characterized by mineralization of the skin and elastic tissues. The implications of ABCC6 loss-of-function on pathological mineralization of structures in the spine, however, are unknown. Using the ABCC6-/- mouse model of PXE, we investigated age-dependent changes in the vertebral bone and intervertebral disc. ABCC6-/- mice exhibited diminished trabecular bone quality parameters at 7-months which remained significantly lower than the wild-type mice at 18 months-of-age. ABCC6-/- vertebrae showed increased TRAP staining along with decreased TNAP staining, suggesting an enhanced bone resorption as well as decreased bone formation. Surprisingly, however, loss of ABCC6 resulted only in a mild, aging disc phenotype without evidence of dystrophic mineralization. Finally, we tested the utility of oral K3Citrate to treat the vertebral phenotype since it is shown to regulate hydroxyapatite mechanical behavior. The treatment resulted in inhibition of osteoclastic response and an early improvement in mechanical properties of the bone underscoring the promise of potassium citrate as a therapeutic agent. Our data suggest that although ectopic mineralization is tightly regulated in the disc, loss of ABCC6 compromises vertebral bone quality and dysregulates osteoblast-osteoclast coupling.